Identification of carcinogens within the IARC monograph program. - Vainio, Harri; Wilbourn, J. (Scandinavian Journal of Work, Environment & Health, 1992)
Fewer than 50 chemicals, groups of chemicals, or mixtures have been causally linked with cancer in humans. Some 250 chemicals have, however, been found to be carcinogenic to rodents. Carcinogenic risk factors that have been identified for humans occur in clearly quantifiable exposure situations, but epidemiologic information on cancer in humans is missing or inadequate for the great majority of chemicals. Extrapolation of animal data to humans is complicated because long-term carcinogenicity studies on animals are carried out under simplified conditions, whereas humans are exposed to a multitude of exogenous and endogenous agents. Furthermore, the carcinogenic process includes multistage and multifactorial aspects, and human populations are genetically and physiologically heterogeneous. Although the science of carcinogenesis is making rapid progress in terms of understanding some of these processes and interactions, there is still a need to err on the side of safety and accept animal data as a warning signal for possible human effects.
Keywords: carcinogen; IARC; IARC monograph; International Agency for Research on Cancer